17 Outcome of extra-corporeal life support for fulminant heart failure/cardiogenic shock. (7th October 2015) - Mahon, N; O'Neill, J; O'Brien, S; McCarthy, J; O'Loughlin, C; Carton, E
Abstract : Background: Fulminant heart failure (so called 'crash and burn') are associated with a grim prognosis, and the outcomes of ventricular assist device (VAD) implantation in this group are poor. Accordingly extracorporeal life support (ECLS) systems have emerged as options for stabilisation of these patients allowing for a more definitive intervention at a later stage ('bridge to decision' or 'bridge to bridge'). Aim and methods: To evaluate ECLS outcomes for fulminant heart failure / cardiogenic shock (CS) and to compare these with ECLS outcomes for other indications. A systematic review of all cases of ECLS for cardiac indications in one institution since program inception was undertaken. Results: Between 2009 and 2015, 37 patients underwent cardiac ECLS (Cardiohelp® Maquest, Germany) for a median of 5 days range (range: 1–13 days) and a total of 193 ELCS days. Fourteen patients (37%) had CS, 16 patients (43%) had post-cardiotomy cardiogenic shock (PCCS) and 7 patients (19%) had ECLS during cardiopulmonary resuscitation (ECPR). Survival to hospital discharge was 75% and 57% among the PCCS and ECPR groups respectively. Of the 14 CS patients, 3 (21%) survived, one to hospital discharge ('bridge to recovery') and 2 to VAD implantation as bridge to transplantation ('bridge to bridge'). The remaining 11 CS patients were deemed unsuitable for further intervention and did not survive. Conclusion: ECLS for fulminant heart failure can be life saving. However, expectations should be tempered by the fact that overall outcomes in this group remains poor. While certain presentations, such as fulminant myocarditis, can neither be prevented nor predicted, in less acute situations timely recognition of patients who might ultimately require cardiac transplantation is desirable.